2022
DOI: 10.1007/s10914-022-09614-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical, Ontogenetic, and Genomic Homologies Guide Reconstructions of the Teeth-to-Baleen Transition in Mysticete Whales

Abstract: The transition in Mysticeti (Cetacea) from capture of individual prey using teeth to bulk filtering batches of small prey using baleen ranks among the most dramatic evolutionary transformations in mammalian history. We review phylogenetic work on the homology of mysticete feeding structures from anatomical, ontogenetic, and genomic perspectives. Six characters with key functional significance for filter-feeding behavior are mapped to cladograms based on 11 morphological datasets to reconstruct evolutionary cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 129 publications
0
17
0
Order By: Relevance
“…The uncertainty over the evolutionary relationships of this group is probably due to convergent evolution of similar filter feeding modes displayed in specimens found in different parts of the world, as well as to the unique mixture of traits they presented (Berta et al, 2016). For example, some of them had short baleen plates that closely resemble the morphology of Caperea (Marx et al, 2017), which has been proposed to be included as the last living representative of the group (Fordyce & Marx, 2013), although this is still debated (Berta et al, 2016; Gatesy et al, 2022), but lacked some morphological features seen in the modern species. Similar fossils from the same locality have been found with fish fossilized in their stomach, hinting that they had a diet more similar to modern rorquals in contrast with the copepod‐specialist pygmy right whales (Collareta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty over the evolutionary relationships of this group is probably due to convergent evolution of similar filter feeding modes displayed in specimens found in different parts of the world, as well as to the unique mixture of traits they presented (Berta et al, 2016). For example, some of them had short baleen plates that closely resemble the morphology of Caperea (Marx et al, 2017), which has been proposed to be included as the last living representative of the group (Fordyce & Marx, 2013), although this is still debated (Berta et al, 2016; Gatesy et al, 2022), but lacked some morphological features seen in the modern species. Similar fossils from the same locality have been found with fish fossilized in their stomach, hinting that they had a diet more similar to modern rorquals in contrast with the copepod‐specialist pygmy right whales (Collareta et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship between tooth development and the evolution of keratinized innovations of the feeding apparatus was proposed in several toothless mammals [1,14,15,61]. In cetaceans, several studies [62,63] proposed that the neurovascular anatomy of the upper teeth was co-opted for nourishing baleen. Lanzetti [14] showed that baleen rudiments develop alongside tooth germs within the alveolar canals of minke whales.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty over the evolutionary relationships of this group is probably due to convergent evolution of similar filter feeding modes displayed in specimens found in different parts of the world, as well as to the unique mixture of traits they presented (Bisconti, 2015; Gol’din et al, 2015; Berta et al, 2016). For example, some of them had short baleen plates that closely resemble the morphology of Caperea (Marx et al, 2017), which has been proposed to be included as the last living representative of the group (Fordyce and Marx, 2013; Marx et al, 2019), although this is still debated (Berta et al, 2016; Gatesy et al, 2022), but lacked some morphological features seen in the modern species.…”
Section: Discussionmentioning
confidence: 99%